Reading habit among the students in Sekolah Kebangsaan Seri Paka, Paka, Dungun,Terengganu - Zanariah, Nawawi; Hasmadi, Hassan (Universiti Malaysia Pahang, 2021)
Reading is the bridge of knowledge. Reading is a tool needed by learners to understand all other subjects. Children begin to develop lifelong attitudes toward reading in the home. Parents are the first person being identified as the agents that can enrich the language environment of a community. Anyhow, teachers play important role to cultivate good reading habits among the students. Nowadays, the children are exposed to varieties of funky gadgets which slowly taking a steady control over individual lives and gradually vanish the reading habits among them. This phenomenon will affect the quality and achievement of education in the country. The study examined the students’ reading habits, the purpose of reading and the hindrances to reading. Two hundred and twenty primary school pupils were drawn to answer the questionnaires. Participants were mainly drawn from standard four, five and six. Their ages ranged from 10 – 12 years old. Results further showed that pupils spent most of the time watching television and playing games rather than reading. The availability and accessibility for reading such as convenient facilities and reading materials were provided by parents and school library. Variety of reading materials and furnishing school libraries could not attract them towards love and choose reading as habit. Yet, they refused to read during their free time. They read just to pass the examination and not for being well-informed person. Recommendations based on the results of the study for parents, teachers and schools are highlighted